A Theology of Alterity : Levinas, von Balthasar, and Trinitarian Praxis - Morrison, Glenn (Book collections on Project MUSE., 2013)
"Strives to radically utilize Emmanuel Levinas's philosophical framework, bringing it into conversation with the theology of Hans Urs von Balthasar, to construct a post-ontotheological account of theology that unites theory and praxis. By allowing Levinas's Judaism to challenge von Balthasar's Catholicism, Glenn Morrison develops a perspective that is both theologically rich and philosophically provocative"--Provided by publisher.